Outcomes of Pioglitazone and Metformin on Anthropometric, Metabolic and Endocrine variables in POS - Ayesha Khan, Mamoora Arslaan, Asra Khan Pahore, Hafiza Tuseef Sayyar, Nasim Karim (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate the outcomes of Pioglita zone and Metformin on anthropometric, metabolic and endocrine variables in PCOS. Methods: This randomized controlled trial was executed at Pharmacology Department of Bahria University Medical and Dental College in collaboration with Mamji Hospital Karachi from September 2018 to March 2019. Eighty PCOS infertile patients as per Rotterdam 2003 criteria,aged 20-40 years were enrolled. They were divided into two groups of 40 patients each by using computer generated numbers. All patients had fasting insulin levels of >9 μU/mL, serum glucose levels ≥126 mg/dl and suffering from oligomenorrhoea or amenorrhoea. Group A received Tablet Pioglitazone 30 mg once daily and group B was given tablet Metformin 500 mg for three months along with lifestyle changes. Results: Sixty-one participants completed the study. Anthropometric variables included weight, BMI and W/H ratio. Metformin treated group reduced more weight and BMI as compared to Pioglitazone. Metabolic variables included glycaemic indices, lipid profile and hs-CRP estimation. Pioglitazone group improved glycaemic indices more compared to Metformin. Serum progesterone level was significantly increased in Pioglitazone group (5.20±1.18) than Metformin group. Pioglitazone produced more ovulation in comparison to Metformin. Hence it is proved that it is better option in those patients who are unable to tolerate Metformin and cannot continue treatment for infertility. Conclusion: Pioglitazone group produced highly significant increase in serum progesterone level indicating ovulation and improved insulin resistance than the metformin group. Keywords: Female infertility, ovulation induction, Metformin, Pioglitazone, polycystic ovarian syndrome